Effect of segregations on mechanical properties and crack propagation in spring steel - B. Žužek; M. Sedlacek; B. Podgornik (Fracture and Structural Integrity)
Considerable efforts have been made over the last decades to improve performance of spring steels, which would increase the service time of springs and also allow vehicles weight reduction. There are different possibilities of improving properties of spring steels, from modifying the chemical composition of steels to optimizing the deformation process and changing the heat treatment parameters. Another way of improving steel properties is through refining the microstructure and reducing amount of inclusions. Therefore, the focus of the current investigation was to determine the effect of more uniform and cleaner microstructure obtained through electro-slag remelting (ESR) of steel on the mechanical and dynamic properties of spring steel, with special focus on the resistance to fatigue crack propagation. Effect of the microstructure refinement was evaluated in terms of tensile strength, elongation, fracture and impact toughness, and fatigue resistance under bending and tensile loading. After the mechanical tests the fracture surfaces of samples were analyzed using scanning electron microscope (SEM) and the influence of microstructure properties on the crack propagation and crack propagation resistance was studied. Investigation was performed on hot rolled, soft annealed and vacuum heat treated 51CrV4 spring steel produced by conventional continuous casting and compared with steel additional refined through ESR. Results shows that elimination of segregations and microstructure refinement using additional ESR process gives some improvement in terms of better repeatability and reduced scattering, but on the other hand it has negative effect on crack propagation resistance and fatigue properties of the spring steel.